A Critical Discourse Analysis of ‘A Guide to Boycotting for Palestine’ on the ‘Let’s Talk Palestine’ Instagram Account Using Fairclough’s Three-Dimensional Model (PANOPTICON: Journal of English Studies, 2024)
This study aims to investigate the use of written communication on an Instagram post. Specifically, the power contained in the communication and its influence for the audiences. In purpose to reveal the implied meaning of the messages, by examining the diction used, sentence form and the topography in a written communication. This study applied a qualitative descriptive method to help in arranging this study. This study found the relationship between the word used and the author ideology in an instagram post which can be known as a form of discourse. The examined data shows that the repetition of words ‘BDS’ and ‘Boycott’ has a power to build up the content. With the depicted symbols as the target of the ‘BDS’ and 'Boycott’ action, the author uses his/her authority to influence the readers persuasively. The writers conclude that the object is conveying the author’s message to persuade the audiences with the use of language. Further, this study focuses on an Instagram post entitled, “A Guide to Boycotting for Palestine” by the “Let’s Talk Palestine” Instagram account.